The Right Anterior Intraparietal Sulcus Is Critical for Bimanual Grasping: A TMS Study. (3rd May 2013) - Le, Ada; Vesia, Michael; Yan, Xiaogang; Niemeier, Matthias; Crawford, J. Douglas
Abstract : Grasping with 2 limbs in opposition to one another is older than the hand, yet the neural mechanisms for bimanual grasps remain unclear. Similar to unimanual grasping, bimanual grasping may require regions in the parietal cortex that use visual object-feature information to find matching stable grasp points on the object. The localization of matching points is computationally expensive, so it might make sense for the signals to converge in a single cortical area. To examine this, we use transcranial magnetic stimulation (TMS) to probe the contribution of cortical areas known to be associated with unimanual grasping, while participants performed bimanual grasps. We applied TMS to the anterior and caudal portion of the intra-parietal sulcus (aIPS and cIPS) in each hemisphere during a size-perturbation task using the index fingers of both hands to grasp an object whose orientation might or might not change. We found significant interaction effects between TMS and perturbation of the grasp-relevant object dimension that increased grip aperture only for the right aIPS. These results indicate that the aIPS is involved not only in unimanual, but also bimanual grasping, and the right aIPS is critically involved in bimanual grasps. This suggests that information from both hemispheres converges in the right hemisphere to achieve bimanual grasps.